Breaking up sitting with short frequent or long infrequent physical activity breaks does not lead to compensatory changes in appetite, appetite-regulating hormones or energy intake. (1st March 2023) - Maylor, Benjamin D.; Zakrzewski-Fruer, Julia K.; Stensel, David J.; Orton, Charlie J.; Bailey, Daniel P.
Abstract: The aim of this study was to determine the appetite-related responses to breaking up prolonged sitting with physical activity bouts differing in frequency and duration among adult females. Fourteen sedentary females aged 34 ± 13 years with a body mass index of 27.1 ± 6.3 kg/m 2 (mean ± SD) took part in a randomised crossover trial with three, 7.5 h conditions: (1) uninterrupted sitting (SIT), (2) sitting with short frequent 2-min moderate-intensity walking breaks every 30 min (SHORT-BREAKS), and (3) sitting with longer duration, less frequent 10-min moderate-intensity walking breaks every 170–180 min (LONG-BREAKS). The intensity and total duration of physical activity was matched between the SHORT-BREAKS and LONG-BREAKS conditions. Linear mixed models were used to compare the outcomes between conditions with significance being accepted as p ≤ 0.05. There were no significant between-condition differences in hunger, satisfaction, prospective food consumption or overall appetite area under the curve (AUC) (all p ≥ 0.801). Absolute ad libitum energy intake and relative energy intake (REI) did not differ significantly between conditions (all p ≥ 0.420). Acylated ghrelin and total peptide YY incremental and total AUC did not differ significantly between conditions (all p ≥ 0.388). Yet, there was a medium effect size for the higher acylated ghrelin incremental AUC in SHORT-BREAKS versus SIT (d = 0.61); the reverse was seen for total AUC, which was lower in SHORT-BREAKS versus SIT (d = 0.69). These findings suggest that breaking up sitting does not lead to compensatory changes in appetite, appetite hormones or energy intake regardless of physical activity bout duration and frequency among adult females.